Postsynaptic nanodomains generated by local palmitoylation cycles. (7th April 2015) - Fukata, Masaki; Sekiya, Atsushi; Murakami, Tatsuro; Yokoi, Norihiko; Fukata, Yuko
Abstract : Precise regulation of protein assembly at specialized membrane domains is essential for diverse cellular functions including synaptic transmission. However, it is incompletely understood how protein clustering at the plasma membrane is initiated, maintained and controlled. Protein palmitoylation, a common post-translational modification, regulates protein targeting to the plasma membrane. Such modified proteins are enriched in these specialized membrane domains. In this review, we focus on palmitoylation of PSD-95, which is a major postsynaptic scaffolding protein and makes discrete postsynaptic nanodomains in a palmitoylation-dependent manner and discuss a determinant role of local palmitoylation cycles in creating highly localized hotspots at the membrane where specific proteins concentrate to organize functional domains.